Business Environment Variables as Determinants of Sustainable Profitability of Small and Medium Scale Enterprises (SMEs) in Ibadan Metropolis - OLUWADARE, Dorcas E.; GBADAMOSI, Tolulope V. (Ilorin Journal of Education, 2025)
SMEs significantly drive economic growth and poverty reduction in emerging economies like Nigeria, especially in cities such as Ibadan. However, many face challenges affecting sustainability. This study examines key determinants of SME profitability in Ibadan, using a correlational descriptive design using mixed method of quantitative and qualitative research and a multi-stage sampling procedure. The samples were 100 petty traders which cut across the 10 sampled areas in Ibadan, the metropolis. A questionnaire on Business Variables as Determinant of Sustainable Profitability of SMEs (r = 0.79) using Cronbach Alpha and an Interview Guide for Small and Medium Scale Enterprises was used to collect the quantitative and qualitative data respectively. Person Product Moment Correlation (PPMC) and thematic approach were used to analyse the quantitative and qualitative data respectively. The findings revealed that there was significant relationship between access to finance and profitability of SMEs (r (99) = .195p <0.05); significant relationship between application of Information and Communication Technology (ICT) and profitability of SMEs (r (99) = .205p <0.05) and significant relationship between entrepreneurial training and profitability of SMEs (r (99) = .122p <0.05) and the effect of access to finance, entrepreneurial training, application of ICT and the profitability of SMEs got the value of R =.432, while R² = .186. This suggests that all the factors combined together accounted for (Adj.R²= .125) variance in the prediction of profitability of SMEs. In line with the quantitative findings, interview results showed most SMEs were internally financed, valued ICT for efficiency and interaction, and saw training as highly beneficial. The study concluded that these determinants are vital for sustainable profitability and long-term survival. It is recommended that the government support SMEs by optimizing access to finance, ICT tools, and training opportunities to enhance their performance and ensure profitability over time.